A novel approach for non-enzymatic determination of urea via a screen-printed electrode prepared with a conductive ink containing graphene and nickel oxide - Kurteli, Rabianur; Dokur, Ebrar; Uruc, Selen; Gorduk, Ozge; Sahin, Yucel (ROYAL SOC CHEMISTRY, 2025)
Development of conductive inks for the fabrication of flexible sensors designed for the determination of various biological compounds represents a promising approach. In this study, a non-enzymatic conductive ink for urea detection is developed using nitrogen-doped graphene and nickel oxide nanoparticles. The screen printing technique was used to prepare a flexible electrochemical paper-based electrode utilizing the conductive ink. In order to create disposable electrodes that exhibit high electrical conductivity and strong integration into a flexible substrate, it is essential to consider the production process and components of the inks. The prepared Graphite/NiO/N-doped Graphene/Screen-Printed Electrode (G/NiO/N-Gr/SPE) is subjected to a series of electrochemical and morphological characterization studies, including cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS), Fourier-transform infrared (FTIR) spectroscopy, X-ray photoelectron spectroscopy (XPS) and scanning electron microscopy (SEM). The electrochemical detection of urea was conducted using the G/NiO/N-Gr/SPE. The electrode exhibits a linear range of detection of 0.5 to 1000 mu M, with a limit of detection (LOD) of 0.32 mu M. This innovative urea sensor demonstrates promising potential for the analysis of urea in saliva and urine samples.
Keywords: ELECTROCHEMICAL SENSOR; DOPAMINE; ACID; Chemistry